Efficacy and safety of piperacillin–tazobactam compared with meropenem in treating complicated urinary tract infections including acute pyelonephritis due to extended-spectrum β-lactamase-producing Enterobacteriaceae - Zhang, Wei; Yan, Chun-Yu; Li, Shu-Rui; Fan, Ting-Ting; Cao, Shan-Shan; Cui, Bin; Li, Meng-Ying; Fan, Bo-Yuan; Ji, Bo; Wang, Li; Cui, Fei; Cui, Jia; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
Extended-spectrum β-lactamase (ESBL)-producing Enterobacteriaceae pose a huge threat to human health, especially in the context of complicated urinary tract infections (cUTIs). Carbapenems and piperacillin–tazobactam (PTZ) are two antimicrobial agents commonly used to treat cUTIs. A monocentric retrospective cohort study focused on the treatment of cUTIs in adults was conducted from January 2019 to November 2021. Patients with a positive urine culture strain ≥ 103 colony-forming units per milliliter (CFU/mL) that is sensitive to PTZ and carbapenems were included. The primary endpoint was clinical success after antibiotic therapy. The secondary endpoint included rehospitalization and 90-day recurrence of cUTIs caused by ESBL-producing Enterobacteriaceae. Of the 195 patients included in this study, 110 were treated with PTZ while 85 were administered meropenem. The rate of clinical cure was similar between the PTZ and meropenem groups (80% vs. 78.8%, p = 0.84). However, the PTZ group had a lower duration of total antibiotic use (6 vs. 9; p < 0.01), lower duration of effective antibiotic therapy (6 vs. 8; p < 0.01), and lower duration of hospitalization (16 vs. 22; p < 0.01). In terms of adverse events, the safety of PTZ was higher than that of meropenem in the treatment of cUTIs.